2018
DOI: 10.15419/bmrat.v5i9.475
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of UHRF1 and P16INK4A expression levels in newly diagnosed AML patients

Abstract: Introduction: Gene mutation is an infrequent cause of tumor suppressor gene (TSG) defect in de novo AML patients. Instead, it seems that leukemic cells employ epigenetic tricks to attenuate the negative impacts of intact TSGs. Ordinarily, critical TSGs, such as p16INK4A, is hyper-methylated in AML blasts under the impact of master epigenetic regulators, such as UHRF1. In this study, we investigated the correlation between UHRF1 and p16INK4A gene expression levels in newly diagnosed AML patients. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…We previously showed that p16 INK4A expression varies among different age groups of AML patients and healthy subjects, as we found that the p16 INK4A expression was inversely correlated with aging among AML patients, contrariwise the healthy subjects [27]. In the present study, we found that the lower levels of p53 expression were also signi cantly skewed to older patients (r = -0.348, P-value = 0.019).…”
Section: The Gene Expression Patterns Of P16 Ink4a and P53 Changed Bysupporting
confidence: 68%
“…We previously showed that p16 INK4A expression varies among different age groups of AML patients and healthy subjects, as we found that the p16 INK4A expression was inversely correlated with aging among AML patients, contrariwise the healthy subjects [27]. In the present study, we found that the lower levels of p53 expression were also signi cantly skewed to older patients (r = -0.348, P-value = 0.019).…”
Section: The Gene Expression Patterns Of P16 Ink4a and P53 Changed Bysupporting
confidence: 68%